Managing Software Development Projects for Success: Aligning Plan- and Agility-Based Approaches to Project Complexity and Project Dynamism. Issue 3 (June 2020) - Butler, Charles W.; Vijayasarathy, Leo R.; Roberts, Nicholas
In general, project complexity and project dynamism are recognized as potent characteristics that influence, usually in a negative way, the outcome of software development projects. However, with respect to the two dominant paradigms for managing software development projects (i.e., plan-based project approach and agility-based project approach), there is less agreement as to which one is better. Emerging research suggests that the preeminence of one approach over another is a matter of fit between the project management approach and the project context, including its complexity and dynamism. We contribute to this line of research by studying the moderating influence of the two project management approaches on the relationship between project complexity and project dynamism on project outcomes. Our analysis of data gathered from a survey of software development professionals shows that managing dynamism is critical for realizing project success, and an agility-based project approach is best suited for mitigating dynamism's negative effects on project success.